Symposium 10: Phenomenography and Networked Learning - Hodgson, Vivien; Houldsworth, Elizabeth; Booth, Shirley; Hultén, Magnus (Proceedings of the International Conference on Networked Learning, 2002)
This paper reports on a phenomenographic study which aimed to understand the technology-supported learning experience of 20 managers. A brief review of the relevant literature is presented including learning orientations; study approaches and management learning before findings from the interview are discussed. The findings from the interview reveal three different categorisations of learners’ experience: instrumental compliance, speculative opportunism and reflective learning. The categorisations are considered relevant as they are supported by considerable detail from the interviews and resonate with prior studies and literatures. Also interesting is the commercial context in which they emerged, which differs from the academic setting of most prior work. Papers: Phenomenological Enquiry into Manager Learning Orientation and Study Approach When Learning with Technology Elizabeth Houldsworth and Vivien Hodgson Opening the variation in web-based discussion: an empirical study Shirley Booth and Magnus Hultén Considering context for networked learning in a phenomenographic perspective Magnus Hultén and Shirley Booth